Characterization of two new degradation products of atorvastatin calcium formed upon treatment with strong acids - Krauß, Jürgen; Klimt, Monika; Luber, Markus; Mayer, Peter; Bracher, Franz (Beilstein Journal of Organic Chemistry, 2019)
Atorvastatin calcium (Lipitor®, Sortis®) is a well-established cholesterol synthesis enzyme (CSE) inhibitor commonly used in the therapy of hypercholesterolemia. This drug is known to be sensitive to acid treatment, but only little data has been published on the structures of the degradation products. Here we report the identification of two novel degradation products of atorvastatin, which are formed only under drastic acidic conditions. While treatment with conc. sulfuric acid led to a loss of the carboxanilide residue (accompanied by an expectable lactonization/dehydration process in the side chain), treatment with conc. aqueous hydrochloric acid gave a complex, bridged molecule under C–C-bond formation of the lactone moiety with the pyrrole, migration of the isopropyl group and loss of the carboxanilide residue. The novel degradation products were characterized by NMR spectroscopy, HRMS data and X-ray crystal structure analysis.
Keywords: atorvastatin; crystal structure; cyclization; degradation products; fragmentation; stress test